STRATEGI PENGEMBANGAN SPIRITUAL TOURISM BERBASIS COMMUNITY-BASED UNTUK PENGUATAN EKONOMI MASYARAKAT SEKITAR CANDI PRAMBANAN - Heni Dwi Lestari; Sri Wahyuni; Meiana Maulida Hikmawati (Jurnal Pariwisata Tawangmangu, 2026)
This study aims to analyze the development strategy of Community-Based Tourism (CBT) based spiritual tourism to strengthen the local economy surrounding Prambanan Temple. The shift in tourism toward meaningful, sustainable experiences has heightened the importance of spiritual tourism as an alternative development model. The study employed a descriptive quantitative approach supported by qualitative analysis. Data were collected through questionnaires, observations, in-depth interviews, and documentation involving 300 respondents consisting of local community members, tourism business actors and community leaders. Data were analyzed using descriptive analysis, SWOT analysis, and Value Chain Analysis to identify community perceptions, economic impacts, and appropriate development strategies. The findings indicate that community perceptions of spiritual tourism development are highly positive, with an average score of 4.24, while perceptions of its economic impact reached 4.14. Spiritual tourism is considered capable of increasing income, expanding employment opportunities, and supporting the growth of local SMEs. SWOT analysis places the development strategy in Quadrant I (Growth Strategy), indicating strong internal strengths and favorable external opportunities. Value Chain Analysis shows that the greatest economic benefits are generated through SMEs, local culinary businesses, homestays, tour guide services, transportation, and cultural handicrafts. CBT-based spiritual tourism has strong potential to improve community welfare while preserving cultural and spiritual values. Strengthening community participation, developing local tourism products, enhancing digital promotion, and increasing stakeholder collaboration are recommended to support sustainable tourism development around Prambanan Temple.